Soccer vs. flatwater and slalom kayak, in relation to bone density and muscle mass in male competitors - Chrysikopoulos, K.; Diafas, V.; Kaloupsis, S.; Maridaki, M.; Sotiropoulos, A.; Koutedakis, Y. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
We investigated the effects of different weight-bearing and non weight-bearing physical activities on bone mineral density (BMD) and appendicular muscle mass (AMM) in male competitors. One hundred-six male (aged 18-26 yrs) volunteered. The sample included flatwater kayakers (Kflat; n = 22), slalom kayakers (Kslalom; n = 19), and socc er players (S; n = 33) who competed at national and international level. Thirty two age-matched non athletic individuals served as controls (C). All competitors exercised regularly at least 8 yrs for an average of 10 mo per year, 6 d•wk-1 for a minimum of 3 h•d-1. Segmental, total BMD and AMM were assessed with a dual-energy x-ray absorptiometry (DEXA). DEXA analysis also includes bone mineral content (BMC) and fat and lean masses. Total BMD was significantly higher (p < 0.01) in flatwater kayakers (mean ± SD: 1.31 ± 0.16 g•cm-2), slalom kayakers (1.36 ± 0.14 g•cm-2) and soccer players (1.47 ± 0.17 g•cm-2) than the C group (1.18 ± 0.13 g•cm-2) while soccer players revealed the highest. Soccer players had significantly higher regional BMD of the legs (1.59 ± 0.18 g•cm-2) compared with the three groups (p < 0.05). AMM was significantly higher (p < 0.01) in all three athletic groups (Kflat: 32.9 ± 3.2 kg; Kslalom: 31.2 ± 3.9 kg; S: 35.3 ± 4.4 kg) compared with C (26.4 ± 3.9 kg). Body fat percentage (% weight) was significantly lower (p < 0.05) in all competitors (Kslalom: 13.2 ± 5.1; Kflat: 11.0 ± 3.5 and S: 8.4 ± 3.1 kg) than the C group (17.5 ± 7.1 kg). Individuals engaged in competitive weight-bearing activities (soccer players) and also non weightbearing activities (flatwater and slalom kayakers), have significantly higher total BMD and AMM than controls. These results suggest that competing either in weight or non weight-bearing activities may be an important factor in achieving a high peak bone mass and reducing osteoporosis risk in elite male competitors.